Water User Associations (WUAs) in Kyrgyzstan : A Case Study on Institutional Reform in Local Irrigation Management - Jenniver Sehring (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2005)
This article aims to give an overview over the reform of local irrigation management by its transfer to Water User Associations and to identify obstacles for its success. Its main focus are institutional aspects of the reform and not technical issues. Institutions are understood as formal as well as informal rules - societal accepted ways of behavior, which can be laws, traditions, norms and values. A subtype of institutions are organizations as the ones that enforce those rules but are also shaped by these. 3 The existing institutions are still active Soviet ones as well as pre-Soviet and post-Soviet norms and rules that emerged after the decline of the binding power of the Soviet system. Water management is nested into certain cultural norms of behavior that limit the compliance to rules that are not perceived as legitimately. The study therewith combines rationalistic and constructivist approaches of NeoInstitutionalism by analyzing incentives influencing actors' choices but also by assessing the role cultural and societal norms and values play in determining appropriate choices.
Keywords: 330; Bewässerung; Wasserversorgung; Wasserpolitik; Kirgisistan